2004
DOI: 10.1017/s0952836904005503
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in head shape and diet in the cottonmouth snake (Agkistrodon piscivorus)

Abstract: Sexual dimorphism is a common phenomenon among animals. The usual cause cited for sexual dimorphism in animals is sexual selection acting through female choice or male-male combat. Natural selection acting to reduce resource competition between the sexes, however, is an important alternative evolutionary scenario, but this possibility has received little empirical study. Here this issue is addressed by examining the relationships among body size, head shape and the functional aspects of diet in the adult male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
9

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 28 publications
2
73
0
9
Order By: Relevance
“…The lack of expression differentiation in A. piscivorus highlights the significance of the differentiation in S. miliarius and C. adamanteus and suggests that different evolutionary processes are responsible for these different patterns. The geographic variation in protein expression for C. adamanteus and S. miliarius is consistent with local adaptation as a result of variable selective pressures owing to genotype-by-genotype-by-environment interactions, and the lack of expression variation in A. piscivorus may be a result of diffuse selection owing to its generalist diet (Vincent et al 2004) or high levels of gene flow (but see later). We next examined whether this differentiation in expression level for C. adamanteus and S. miliarius was biased toward high-or low-expression proteins.…”
Section: Resultssupporting
confidence: 54%
“…The lack of expression differentiation in A. piscivorus highlights the significance of the differentiation in S. miliarius and C. adamanteus and suggests that different evolutionary processes are responsible for these different patterns. The geographic variation in protein expression for C. adamanteus and S. miliarius is consistent with local adaptation as a result of variable selective pressures owing to genotype-by-genotype-by-environment interactions, and the lack of expression variation in A. piscivorus may be a result of diffuse selection owing to its generalist diet (Vincent et al 2004) or high levels of gene flow (but see later). We next examined whether this differentiation in expression level for C. adamanteus and S. miliarius was biased toward high-or low-expression proteins.…”
Section: Resultssupporting
confidence: 54%
“…Conversely, behaviors such as territory defense, display or brood care may place demands on the trophic apparatus that compromise feeding performance; for example, enlargement of the buccal cavity in mouth-brooding male cardinalfishes could compromise suction-feeding ability (Barnett and Bellwood, 2005;Wainwright et al, 2007). However, despite extensive study of the kinematics of prey capture (Wainwright et al, 2007;Higham, 2007) and divergence in diet and feeding morphology between the sexes (Vincent et al, 2004;Barnett and Bellwood, 2005;Barnett et al, 2006;Hoey et al, 2012), there appear to be no examples of sexual dimorphism in feeding kinematics.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior has been suggested for M. bifossatus (FERREIRA & OUTEIRAL 1998, LEITE et al 2009, DOURADO et al 2013, and has been observed in species of other genera, such as Coniophanes fissidens (Günther, 1858) (ZUG et al 1979), Dendrophidion dendrophis (Schlegel, 1837) (PRUDENTE et al 2007) and Echinanthera cyanopleura (Cope, 1885) (ZANELLA & CECHIN 2010). The difference in the length of the heads of males and females of M. boddaerti may be related to the exploitation of different resources, which may contribute to reduce intraspecific competition (SHINE 1993, VINCENT et al 2004) between the sexes, since males feed on larger prey (SIQUEIRA et al 2012).…”
Section: Discussionmentioning
confidence: 99%